Structure of epitaxial L1(0)-FePt/MgO perpendicular magnetic tunnel junctions - Kohn, A; Tal, N; Elkayam, A; Kovacs, A; Li, D; Wang, S; Ghannadzadeh, S; Hesjedal, T; Ward, R (2013)
Perpendicular magnetic tunnel junctions (p-MTJs) with MgO barriers are interesting for high-density information-storage devices. Chemically ordered L10-FePt is a potential electrode due to its large perpendicular magnetocrystalline anisotropy. To-date, a single theoretical study on L1 0-FePt/MgO p-MTJ based on an idealized structure reported significant dependence of spin-dependent tunneling on interface structure. [Y. Taniguchi, IEEE Trans. Magn. 44, 2585 (2008).] We report a structural study of epitaxial L10-FePt(001)[110]//MgO(001)[110]//L10-FePt(001)[110] p-MTJs, focusing on the interfaces using aberration-corrected scanning transmission electron microscopy. Interfaces are semi-coherent, with oxygen atomic-columns of MgO located opposite to iron atomic-columns in L1 0-FePt. Up to three lattice planes show atomic-column steps, the origin of which is attributed to antiphase boundaries in L10-FePt. © 2013 American Institute of Physics.